Символика снов и сновидений в контексте интимной психодрамы Тараса Шевченко (попытка архетипического анализа) - Betko, Iryna (Acta Neophilologica, 2022)
The motifs of dreams appear in all literary works written by Taras Shevchenko. They are present, for example, in several lyric poems and fragments of Journal, reflecting important moments in the poet’s intimate psychodrama. The archetypal analysis of their psycho-symbolic content allows one to reveal the specificities of the poet’s inner life, as well as to trace the patterns of animatic projections of his individual unconscious into external reality.